2016
DOI: 10.1111/inm.12238
|View full text |Cite
|
Sign up to set email alerts
|

Care planning for aggression management in a specialist secure mental health service: An audit of user involvement

Abstract: This paper describes an audit of prevention and management of violence and aggression care plans and incident reporting forms which aimed to: (i) report the compliance rate of completion of care plans; (ii) identify the extent to which patients contribute to and agree with their care plan; (iii) describe de‐escalation methods documented in care plans; and (iv) ascertain the extent to which the de‐escalation methods described in the care plan are recorded as having been attempted in the event of an incident. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…2014), and on empirical studies (Hallett & Dickens 2015; Hallett et al . 2016). In its initial UK validation study, it was found to have good psychometric properties including internal reliability, convergent validity, and test–retest reliability.…”
Section: Methodsmentioning
confidence: 99%
“…2014), and on empirical studies (Hallett & Dickens 2015; Hallett et al . 2016). In its initial UK validation study, it was found to have good psychometric properties including internal reliability, convergent validity, and test–retest reliability.…”
Section: Methodsmentioning
confidence: 99%
“…; Hallett et al . ), and many believe that exposure to aggression is an expected ‘part of the job’ (Baby et al . , p. 649) when working with people with acute mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…The frequent occurrence of aggression could lead mental health professionals to view their roles negatively, use extended periods of sick leave, or resign (Edward et al 2014). Mental health nurses (hereafter referred to as 'nurses') are frontline professionals in managing aggression (Boardman & Roberts 2014;Bowers et al 2009;Hallett et al 2016), and many believe that exposure to aggression is an expected 'part of the job' (Baby et al 2014, p. 649) when working with people with acute mental illness. This belief could lead nurses to view the causes of aggression as predominantly related to the person's psychiatric symptoms or complex pre-existing personality issues (Bowers 2014;Irwin 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations